KETAKSAMAAN CAUCHY SCHWARZ PADA RUANG HASIL KALI DALAM-2 - Sri Maryani (Universitas Jenderal Soedirman, 2009)
Cauchy-Schwarz inequality is an important property on inner product spaces. This inequality can be generalized to 2-inner product spaces. We can be inducted a norm from those inner product spaces and then generalized that norm to 2-norm. This paper will reprove Cauchy-Schwarz inequality used positive semi definite of Gram matrix such that sub-matrix of Gram determinant is non-negative.